Insights into the structure and thermal stability of uranyl aluminate nanoparticles. (11th January 2017) - Chave, Tony; Le Goff, Xavier; Scheinost, Andreas C.; Nikitenko, Sergey I.
Abstract : Synthesis and characterization by HRTEM, XAFS and HTXRD of uranyl aluminate nanocrystals prepared with various uranium loadings and at different calcination temperatures. Abstract : Ultrasonically assisted hydrolytic precipitation of U(vi ) in the presence of mesoporous alumina followed by thermal treatment of a solid precursor enabled the formation of crystallized uranyl aluminate (URAL) nanoparticles (NPs) dispersed in the alumina matrix. The effect of U(vi ) concentration and calcination temperature on the yield of URAL NPs was studied using XRD, XAFS and HRTEM techniques. At 800 °C, URAL NPs ( d ≈ 5 nm) are formed only for a low uranium loading of about 5 wt% whereas for a higher content of uranium, larger U3 O8 NPs ( d ≈ 20 nm) were identified as the principal uranium species. At 500 °C, URAL NPs are formed even for 25 wt% of uranium. The U LIII edge EXAFS spectra pointed out that uranyl cations in URAL are coordinated by bidentate aluminate groups. Presumably URAL is formed during the heating of the 2UO3 ·NH3 ·2H2 O/AlO(OH) precursor. However, high temperature and higher content of uranium promote transformation of URAL to more thermodynamically stable U3 O8 . This process is accompanied by the growth of uranium NPs via the Ostwald ripening mechanism.